The contribution of tax governance rules to improving the quality of the tax system - Moussa, Drid; Mabrouk, Lebbaz (The International tax journal, 2025)
This study seeks to examine in depth the role and contribution of tax governance rules in enhancing the quality and efficiency of the tax system. It emphasizes how effective governance mechanisms can substantially reduce tax evasion and fraudulent practices committed by taxpayers, which have a direct negative impact on the revenues of the public treasury. Since tax revenues represent one of the most essential and stable sources of government financing, improving the quality of the tax system has become a strategic objective that supports fiscal stability and sustainable economic development. The research highlights that weak governance and the absence of transparency and accountability mechanisms often result in inefficiencies and revenue losses, making tax reform a pressing priority for public administrations. The study argues that applying tax governance principles—such as integrity, accountability, transparency, and efficiency—within tax institutions can lead to significant improvements in tax compliance, citizen trust, and administrative performance. Through a thorough analysis of tax governance frameworks, the study demonstrates that the proper and consistent implementation of these principles has a positive and measurable effect on limiting tax evasion and fraud. Consequently, these improvements contribute to increasing tax revenues and strengthening the equity and credibility of the overall fiscal system.